Pharmacokinetics of hydrogen after ingesting a hydrogen-rich solution: A study in pigs. Issue 11 (November 2021) - Ichihara, Genki; Katsumata, Yoshinori; Moriyama, Hidenori; Kitakata, Hiroki; Hirai, Akeo; Momoi, Mizuki; Ko, Seien; Shinya, Yoshiki; Kinouchi, Kenichiro; Kobayashi, Eiji; Sano, Motoaki
Abstract: Drinking hydrogen (H2 )-rich water is a common way to consume H2 . Although many studies have shown efficacy of drinking H2 -rich water in neuropsychiatric and endocrine metabolic disorders, their authenticity has been questioned because none examined the associated pharmacokinetics of H2 . Therefore, we performed the first study to investigate the pharmacokinetics of H2 in pigs given an H2 -rich glucose solution with the aim to extrapolate the findings to humans. We inserted blood collection catheters into the jejunal and portal veins, suprahepatic inferior vena cava, and carotid artery of 4 female pigs aged 8 weeks. Then, within 2 min we infused 500 ml of either H2 -rich or H2 -free glucose solution into the jejunum via a percutaneous gastrostomy tube and measured changes in H2 concentration in venous and arterial blood over 120 min. After infusion of the H2 -rich glucose solution, H2 concentration in the portal vein peaked at 0.05 mg/L and remained at more than 0.016 mg/L (H2 saturation level, 1%) after 1 h; it also increased after infusion of H2 -free glucose solution but remained below 0.001 mg/L (H2 saturation level, 0.06%). We assume that H2 was subsequently metabolized in the liver or eliminated via the lungs because it was not detected in the carotid artery. In conclusion, drinking highly concentrated H2 -rich solution within a short time is a good way to increase H2 concentration in portal blood and supply H2 to the liver. Abstract : Animal experimentation, translational medical research, catheterization, jejunal vein, portal venous blood sampling